Perlindungan Anak Sebagai Landasan Filosofis Dan Sosiologis Batas Usia Perkawinan Dalam Undang-Undang No.16 Tahun 2019 Perspektif Maqasid Asy- Syari'ah Jasser Auda - Rizqa Febry Ayu; Kamsi Kamsi (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2022)
This study examines how Jasser Auda’s maqāṣid asy-syarīʻah view sonchild protection as the basis for determining the age limit for marriage and how Jasser Auda’s maqāṣid asy- syarīʻah view son the philosophical and sociological foundations contained in the marriage age limit in Law No. 16 of 2019 This study uses a qualitative study with a descriptive analytical method with a philosophical and sociological approach. The results of this study indicatethat, First, Jasser Auda’s maqāṣid asy-syarīʻah view on child protection as the basis for determining the age limit for marriage, namely that Jasser Auda’s maqāṣid asy-syarīʻah theory shows that the goal of equalizing the marriage age limit contained in Law No. 16 The year 2019 refers to the concept of child protection as regulated in Law No. 23 of 2002 concerning Child Protection which includes the basic rights of children, the right to protection from violence and discrimination and full justice for children. Second, Jasser Auda’s maqāṣid asy-syarīʻah view of the philosophical and sociological foundations contained in the marriage age limit in Law No. 16 of 2019 using six features of the system theory that Jasser Auda optimized the results according to Cognitive, Openess, Wholeness, Interrelated Hierarchy, Multi Dimensionality and Porposefullnesis Law No. 16 of 2019 is in accordance with maqāṣid asysyarīʻah, realizing the goal of eliminating discrimination against women in accordance with the global era by reforming maqāṣid to wards Human Rights, creating equality between men and women, refers to the environment of society, nationandstate, such as upholding justice and tolerance, achieving a harmonious family.